Differential Scanning Calorimetry as tool in observing thermal and storage stability of recombinant Bromelain - Ismail, Nurul Azira; Amid, Azura (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
It is important to know the thermal and storage behavior of produced protein for the purpose of storage, transport and shelve life during industrial application. Differential Scanning Calorimetry (DSC) is used to measure the thermal and storage stability of recombinant bromelain produced in our laboratory. Recombinant bromelain thermal and storage stability were measured and compared to the commercial bromelain. The purified recombinant bromelain was powderized using freeze drying method and its transition midpoint, crystallinity and enthalpy were recorded. Recombinant bromelain is more stable than commercial bromelain at higher temperature but the stability reduced after 7 days of storage at 4oC although its activity is lower than commercial at day 1 and 7. Higher energy is needed to break the bond between amino acid chains in recombinant bromelain showing by the enthalpy recorded suggesting that recombinant bromelain has good protein structure and conformation compared to commercial.